Impulsive Problems for Fractional Differential Equations with Functional Boundary Value Conditions at Resonance - Bingzhi Sun; Shuqin Zhang; Weihua Jiang (Journal of Function Spaces)
We establish novel results on the existence of impulsive problems for fractional differential equations with functional boundary value conditions at resonance with dim⁡Ker L=1. Our results are based on the degree theory due to Mawhin, which requires appropriate Banach spaces and suitable projection schemes.